Odpowiedzi

2009-11-08T23:39:59+01:00
A)
x^2 + y^2 - 2x - 6y +9 = 0
(x-1)^2 -1 + (y -3)^2 -9 +9 =0
(x-1)^2 + ( y - 3)^2 = 1
TAK
b)
x^2 +y^2 +4y -5 = 0
x^2 + (y + 2)^2 -4 - 5 = 0
x^2 + (y +2)^2 = 9
TAK
c)
x^2 +y^2 -6x +2y + 10 = 0
(x -3)^2 - 9 + ( y +1)^2 -1 +10 = 0
(x - 3)^2 + (y+1)^2 = 0
NIE
d) (x+5)^2 - 25 +(y +1)^2 - 1 +25 = 0
(x+5)^2 + (y + 1)^2 = 1
TAK
e)
(x -1)^2 + (y - 8)^2 -1 - 256 +66= 0
(x-1)^2 + (y -8)^2 = 191
TAK
f)
(x+4)^2 + (y+2)^2 -16 - 4 +16 = 0
(x+4)^2 + (y +2)^2 = 4
TAK
25 3 25